2023
DOI: 10.4081/gh.2023.1198
|View full text |Cite
|
Sign up to set email alerts
|

Where to place emergency ambulance vehicles: use of a capacitated maximum covering location model with real call data

Soheil Hashtarkhani,
Stephen A. Matthews,
Ping Yin
et al.

Abstract: This study integrates geographical information systems (GIS) with a mathematical optimization technique to enhance emergency medical services (EMS) coverage in a county in the northeast of Iran. EMS demand locations were determined through one-year EMS call data analysis. We formulated a maximal covering location problem (MCLP) as a mixed-integer linear programming model with a capacity threshold for vehicles using the CPLEX optimizer, an optimization software package from IBM. To ensure applicability to the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In the location-allocation research area of medical support vehicles (ambulances), Zaffar and colleagues [7] found that the main objective of most state-of-the-art work is related to finding the best distribution of ambulances to maximize coverage and minimize response times. Mohri and Haghshenas [8] analyzed the problem using the Ambulance Location Problem (ALP) as an extension of the Set Coverage Problem introduced by Toregas [9]; Kavhe and Mesgari combined the Maximum Coverage Location Problem (MCLP) and metaheuristics [10]; Hashtarkhani et al proposed the use of MCLP and combinatorial optimization techniques [11]; while Barojas-Payán et al [12] addressed the problem using the p-median problem.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…In the location-allocation research area of medical support vehicles (ambulances), Zaffar and colleagues [7] found that the main objective of most state-of-the-art work is related to finding the best distribution of ambulances to maximize coverage and minimize response times. Mohri and Haghshenas [8] analyzed the problem using the Ambulance Location Problem (ALP) as an extension of the Set Coverage Problem introduced by Toregas [9]; Kavhe and Mesgari combined the Maximum Coverage Location Problem (MCLP) and metaheuristics [10]; Hashtarkhani et al proposed the use of MCLP and combinatorial optimization techniques [11]; while Barojas-Payán et al [12] addressed the problem using the p-median problem.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, there is no known efficient algorithm that can solve all instances of the problem in polynomial time in an NP-hard problem. To reduce computational complexity, some proposals require the list of possible candidate locations in advance or otherwise include in the methodology an approach to decrease the search space [11,21]. Saeidian et al [18] used a GIS to select candidate locations that satisfied the initial conditions, followed by applying a metaheuristic to calculate the optimal location of temporary help centers.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Supply relates to the infrastructure’s locations (eg, health care providers); demand refers to the locations of individuals who are expected to use the infrastructure (eg, patients); and mobility considers the travel costs between demand and supply locations (eg, driving time) [ 10 ]. Identifying areas with limited spatial accessibility enables planners and policy makers to understand the distribution of health service locations and reveal and address spatial inequities [ 11 ].…”
Section: Introductionmentioning
confidence: 99%